Pendampingan Penyusunan Laporan Keuangan Koperasi dengan Menggunakan Excel di Lingkungan Kesra Perumnas Tanjung Karang Permai Mataram - Nur Fitriyah; Herlina Pusparini; Nurabiah Nurabiah (Jurnal Gema Ngabdi, 2021)
This service aims to make savings and loan cooperatives in the Welfare Environment easy to access bank credit through the implementation of a computer-based accounting information system in the process of preparing financial reports and this becomes a pilot model in developing financial statement applications for other types of cooperatives in the city of Mataram. This service method consists of: 1) the first stage where the creation of a computer application for managing the financial statements of savings and loan cooperatives. With this application, it will be easier for administrators to make cooperative financial reports. 2) the second stage, where computer application training for the management of cooperative financial reports. This assistance is carried out in one of the houses of the cooperative management in the Perumnas Welfare environment using their respective laptops and also the assistants visit one of the administrators in their respective homes to be given assistance. This assistance is carried out for a day with 9 cooperative managers from 9 RTs in the Welfare Environment. This mentoring activity went smoothly. All participants enthusiastically followed the event to the end. Participants also considered that this assistance was important and indispensable for cooperative management. Participants hope to be followed up by providing more assistance so that the management can apply the preparation of cooperative financial reports using excel.